2SPD-001 How can we best manage supply shortages of exclusively human molecules for substitution? The example of immunoglobulins. (23rd March 2022) - Ratsimbazafy, V; Bonnet, S; Lestang, C; Jost, J; Reygner, C; Oses, S; Gosse-Boeuf, N; Renon-Carron, F; Marie-Daragon, A; Cournede, A; Fauchais, AL
Abstract : Background and importance: Drug supply shortages that have increased over the past decade were worsened by the SARS-CoV-2 health crisis. Among the products affected are immunoglobulins (IG), essential for substitution in primary immune deficiencies in particular. In contrast with some plasmatic proteins, IG are only produced from blood donations that have decreased. Recently, IG supply was reduced, 42% in our case, mostly affecting intravenous IG (IVIG). Aim and objectives: To identify, among the existing clinical situations, those that should benefit from IG (subcutaneous IG (SCIG) preferentially in primary substitutions; IVIG treatment to as many patients as possible for whom there is no alternative). Material and methods: Meet physicians representing the most important prescribing departments. Take stock of consumption and supply. Identify ways to optimise the use of available IG. Results: The neurology, clinical haematology, internal medicine and paediatrics representatives were brought together at a Medicinal Products and Medical Devices Commission (MPMDC) session. First 6 months of 2021, data on IVIG: Patient number: 168. IVIG mass: 27.8 kg (70.4% of total IG). Treatment number: 510. On average: 27.6 g/patient/month; 3 cures/patient over 6 months. IVIG use: off-label, 27.4%; immune deficiencies, 41.6% (secondary 9 times; primary 1 time); immunomodulation, 31% (of which: idiopathic thrombocytopenic purpura (ITP), 42.3%; Guillain-Barré syndrome, 9.6%; Kawasaki disease, 3.8%; chronic inflammatory demyelinating polyradiculopathy (CIDP), 38.5%; multifocal motor neuropathies, 5.8%). Discussions at MPMDC led to the development of the following ways to cope: 'Switch' as many patients as possible to SCIG. As the dosage of 2 g/kg/cure is indicative, lower the doses gradually and/or space out the courses. Use corticosteroids whenever possible. Use IVIG for life–threatening authorised situations (eg, acute ITP). Reactivate the plasma exchange pathway for immunomodulations. Reduce off–label use. For off–label indications, include patients in therapeutic trials of IVIG. If life–threatening emergency immunomodulation off–label, treat with molecules such as rituximab and use IVIG only during the latency period. Conclusion and relevance: The implementation of these suggestions, while awaiting the publication of the IG indications' hierarchy by the relevant authorities, should optimise management of the shortage. European, or even international, recommendations would be welcome because of the globalisation of supply. References and/or acknowledgements: We acknowledge (in alphabetical order) : Mélodie Billac, Carole Nivet and Martine Raymondeau. Conflict of interest: No conflict of interest